Peningkatan Minat Belajar Peserta Didik Melalui Media Animasi Berbantuan Canva Pada Pembelajaran Fiqih Fase D - Fauziah, Hapsah; Romansyah, Alfi Khoiri (MASAGI : Jurnal Pendidikan Agama Islam, 2025)
This study focuses on improving students' learning interest through animation media assisted by Canva in the Fiqh subject for Phase D at SMP IT Al Mashduqi. Learning interest is an internal drive within an individual that fosters a sense of attraction, desire, and enthusiasm to actively participate in the learning process. Learning interest is not only related to the desire to acquire knowledge but also includes motivation to make consistent efforts to achieve learning goals. However, the reality is that the learning interest of Phase D students, especially in Grade VII of SMP IT Al Mashduqi, remains relatively low. This is evidenced by pre-research observations, which showed that only about 19.35% of the total 31 students demonstrated an interest in learning. Therefore, a solution is needed to enhance this condition, one of which is by applying animation media assisted by Canva. The purpose of this study is to describe the improvement in students' learning interest before and after the implementation of animation media, as well as to examine the application of animation media in increasing students' learning interest in the Fiqh subject for Phase D at SMP IT Al Mashduqi. The method used in this study is Classroom Action Research (CAR). Data collection techniques include observation, interviews, and questionnaires. Data analysis techniques in CAR involve simple statistical formulas to calculate the average and percentage of students' learning interest. Based on the results of the classroom action research conducted over two cycles, an increase in students' learning interest was observed. In Cycle I, students' learning interest reached 74.19%, and it further increased to 90.32% in Cycle II. This indicates that there was a significant improvement in students' learning interest, with an increase of 74.19% from the pre-cycle to Cycle I and an additional increase of 16.13% from Cycle I to Cycle II. Overall, there was a total increase of 70.97% in students' learning activity from the pre-cycle to Cycle II.  Keywords: Learning Interest, Animation Media, Fiqh